FMSI guidelines for return to physical activity after coronavirus pandemics lockdown - Casaco, M.; Pigozzi, F.; Porcelli, S.; Beltrami, G.; Agnello, L.; Parisi, A.; Pecci, C.; Pecorelli, G.; Scorcu, M.; Pecorelli, S. (Medicina dello Sport, 2020)
The lockdown period has certainly put a strain on our psychophysical health and for many it has represented a problem of functional efficiency of our body. In this document the Italian Sports Medicine Federation (FMSI) makes recommendations for the development and the performance of physical exercise sessions for the general population obliged to stay at home, due to the lockdown caused by the Coronavirus pandemics. Such recommendations are made in terms of intensity, frequency, volume and exercise modality, applying what has already been suggested by the Federation itself in the recent Italian Prescription Guidelines for Physical Activity for Healthy Adults. The proposed reconditioning program suggests the respect of a gradual return to physical activity, starting from at least 30-45 minutes every day up to a total of 150-300 minutes per week, combined with muscle strengthening and flexibility exercises. The intensity of the work must vary according to the individual`s physical conditions and age, recommending activities of moderate intensity for most of the week, with a part of the individual sessions carried out at a higher intensity. If the period of isolation led to an increase in body weight, a return to normal weight is absolutely recommended, combining the returning to an active lifestyle with a controlled diet, moderately low in calories and rich in vitamins and with attention to appropriate hydration. Furthermore, an evaluation by a sports medicine specialist may be useful for a correct classification of health conditions and actual physical possibilities, especially for those with chronic diseases` risk factors or people over 50 years of age. For people who have been suffering from Covid-19, after the approval of the infectious disease specialist, but before returning to any kind of physical activity, an evaluation by the specialist is certainly advisable.